Paraná Pine, Araucaria angustifolia: An Ancient-Looking Conifer for Modern Landscapes - Gary W. Knox (EDIS)
Paraná pine is a primitive-looking conifer valued for its unusual horizontal branching, interesting triangular-shaped needles, and neat, symmetrical form. The primitive appearance of this evergreen tree results from its resemblance to and relationship with an ancient group of Araucaria-related conifers that dominated forests more than 145 million years ago. This tree once covered vast areas in southern Brazil, Argentina and Paraguay. Native Americans harvest the seeds for food. It was an important timber tree for European settlers, and it was logged extensively through the 20th century. Now one of the rarest trees in Brazil, Paraná pine is considered critically endangered due to habitat loss and exploitation. This evergreen conifer grows too large for most residential situations, but is best used as an accent or conversation piece in large-scale landscapes. This 3-page fact sheet was written by Gary W. Knox and published by the UF Department of Environmental Horticulture, November 2014.